OPTIMASI FORMULA TABLET PIROKSIKAM MENGGUNAKAN EKSIPIEN LAKTOSA, AVICEL PH-101, DAN AMPROTAB DENGAN METODE SIMPLEX LATTICE DESIGN - Kusuma, Ikhwan Yuda; Prabandari, Rani (Universitas Muhammadiyah Surakarta, 2020)
Piroxicam solubility in water is very small this cause problem in the process of absorption so that it?s required an optimal formula to establish the physical properties of tablet quality for piroxicam tablets. The purpose of this research was creating formulas with the optimal combination of excipients lactose, Avicel pH 101, and piroxicam amprotab to obtain tablets with good physical properties and disolution. Seven piroxicam tablet formulas were made with a combination of lactose, avicel PH-101, and Amprotab on 2 batches. Method for making tablets piroxicam was established by direct compression. Tests included were the physical properties of piroxicam tablets tablets weight uniformity, uniformity of size, hardness, brittleness, disintegration test, as well as dissolution test, and content uniformity. Based on the simplex lattice design method, lactose is a dominant factor to improved the uniformity of tablet?s concentartions. Interaction of two components avicel PH-101 and amprotab is a dominant factor to reduced vulnerability. Interaction of three components lactose, avicel PH-101 and amprotab is a dominant factor to lowered the value coefisien variation of weight uniformity, increased hardness, decreased the disintegration, and improved dissolution of tablets. Selection of the optimum formula was determined by the method of simplex lattice design through diagrams superimposed contour plots and contour plots for obtaining the optimal proportions of each ingredient as follows: lactose (85,154?100%), avicel PH-101 (0?12,437%), and amprotab (0?5,425%).